Meet the experts Mark Richards and Neal Ford on the journey from developer to software architect - Richards, Mark (O'Reilly Media, 2020)
"The journey from developer to software architect is a difficult one. Join us for this edition of Meet the Expert with Mark Richards and Neal Ford, experienced hands-on software architects and coauthors of Fundamentals of Software Architecture, to learn key tips, techniques, and resources to help you along the way."--Resource description page